FAM111B and FANCD2, a dual expression signature, defines a distinct phenotype of pancreatic cancer - Fang Wei; Wanying Li; Ting Zhou; Lijuan Feng; Xianglin Yuan; Lihong Zhang (Cancer Cell International)
Abstract Background Despite various treatment strategies, the incidence and mortality of pancreatic cancer (PC) are among the highest for malignant tumors. Furthermore, there is a lack of effective molecular typing and targeted therapy to treat PC subtypes. Methods Multiplex immunofluorescence experiments were performed to explore the roles of FAM111B, FANCD2, KRAS and TP53 in human PC tissues. Kaplan-Meier survival curves were generated and a nomogram was prepared for prognostic prediction. Protein correlations were analyzed using human PC tissues and TCGA and GEO data. Pathways analysis, immunoanalysis, and drug susceptibility analysis were performed based on information in the TCGA database. Results Our results indicate that expression of FAM111B and FANCD2 is correlated in human PC tissues and comprises a dual expression signature with predictive value for the prognosis of PC. Using information in public databases, we confirmed the oncogenic relevance of FAM111B and FANCD2 in PC and identified a positive correlation between FAM111B, FANCD2, TP53 and KRAS.FAM111B and FANCD2 jointly regulate ferroptosis, mitotic nuclear division, and nuclear division pathways. Both proteins were demonstrated to be positively correlated with markers of CD4 + Th2 cells and PD-L1 in the tumor microenvironment. Furthermore, drug sensitivity analysis suggested that patients with high FAM111B or FANCD2 expression were highly sensitive to chemotherapeutic and targeted drugs, indicating that these proteins may serve as predictors of treatment efficacy. Conclusion Elevated dual expression of FAM111B and FANCD2 is indicative of poor prognosis, alters the immune microenvironment, and exhibits sensitivity to certain therapeutic agents. Consequently, the high FAM111B/FANCD2 expression subtype may represent a novel and distinct phenotype of PC.